MANAJEMEN SUMBER DAYA INSANI DALAM PERSPEKTIF ISLAM - Waode Mabrukah Azzahrah; Idris Prakkasi; Rusdi Prayogah; Sulaeman (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2026)
Islamic Human Resource Management (IHRM) is a human resource management concept that is founded on Islamic values by recognizing human beings as Allah's trustees who possess moral and spiritual responsibilities. Unlike conventional human resource management, which primarily emphasizes organizational efficiency and productivity, IHRM integrates the principles of the Qur'an and Hadith into every managerial function, including planning, recruitment, employee development, placement, and performance evaluation. This approach aims not only to achieve organizational objectives but also to promote individual character development and public welfare (maslahah). This study aims to examine the concept of Islamic Human Resource Management from an Islamic perspective, analyze the implementation of Sharia principles in recruitment and employee development, and identify the role of organizational culture in supporting the application of Islamic values within organizations. This research employed a qualitative approach using a library research method. Data were collected from academic books, national and international scientific journals, and other relevant scholarly documents. The data were analyzed through data reduction, data presentation, and conclusion drawing using a descriptive qualitative approach. The findings indicate that Islamic Human Resource Management is fundamentally based on the principles of amanah (trustworthiness), justice, professionalism, ihsan (excellence), and the concept of the right person in the right position. The implementation of these principles contributes to strengthening organizational culture, improving employee commitment and integrity, and fostering a more ethical, professional, and sustainable working environment within Sharia-based organizations.